1998
DOI: 10.4269/ajtmh.1998.58.461
|View full text |Cite
|
Sign up to set email alerts
|

Three probable cases of Loa loa encephalopathy following ivermectin treatment for onchocerciasis.

Abstract: Over the past nine years, more than 12 million people exposed to Onchocerca volvulus infection have received at least one dose of ivermectin, almost all without serious adverse reactions. Since 1991, however, several cases with neurologic manifestations, including coma, have been reported after ivermectin treatment of persons infected with O. volvulus who also had concomitant Loa loa infection with very high microfilaremia (Ͼ 50,000 microfilariae/ml of blood). In 1995, four criteria were established to define … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
103
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 27 publications
7
103
1
2
Order By: Relevance
“…Ivermectin is used for treatment in many diseases, including loiasis, scabies, onchocerciasis and strongyloidiasis. In the treatment of onchocerciasis with ivermectin, where L. loa is endemic, encephalitis has been reported (Boussinesq et al, 1998;Ducorps et al, 1995;Gardon et al, 1997). In our patient the results of the liver biopsy were compatible with drug-induced hepatotoxicity.…”
Section: Discussionsupporting
confidence: 65%
“…Ivermectin is used for treatment in many diseases, including loiasis, scabies, onchocerciasis and strongyloidiasis. In the treatment of onchocerciasis with ivermectin, where L. loa is endemic, encephalitis has been reported (Boussinesq et al, 1998;Ducorps et al, 1995;Gardon et al, 1997). In our patient the results of the liver biopsy were compatible with drug-induced hepatotoxicity.…”
Section: Discussionsupporting
confidence: 65%
“…20 Rapid clearance of microfilaremia is supposedly responsible for the development of encephalopathy, but only a few studies have examined pretreatment microfilarial density in patients with encephalopathy. 21,22 It has been suggested that a reduction of more than 30,000 mf/mL in 3 days may increase the risk of encephalopathy occurring. 23 This study suggests that raised CRP before treatment may also be a predictive risk factor for mild reactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, individuals harbouring high microfilaraemias may, exceptionally, develop serious spontaneous neurological or renal complications (Cauchie et al 1965 ;Zuidema, 1971). More significantly, it is well known that high microfilarial (mf) loads are associated with a risk of developing neurological serious adverse events (SAEs) after treatment with the filaricidal drugs diethylcarbamazine (DEC) and ivermectin (Fain, 1978 ;Carme et al 1991 ;Gardon et al 1997 a ;Boussinesq et al 1998). Thus, following ivermectin treatment, it has been demonstrated that individuals presenting with high mf loads (>8000 mf/ml), and those with very high mf loads (>30 000 mf/ml) had, respectively, an increased risk of developing severe adverse reactions without neurological involvement, and SAEs (Gardon et al 1997 a).…”
Section: Introductionmentioning
confidence: 99%